INCREASING TEACHERS' CREATIVITY IN TEACHING THROUGH THE IMPLEMENTATION OF AUDIO-VISUAL MEDIA AT SMP NEGERI 4 DUMAI - Suryani, Leni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is based on the teachers’ low creativity at SMP Negeri 4 Dumai. Therefore, it is necessary to take an action to overcome this problem through the implementation of audio-visual media. Based on the description regarding the identification and limitation of the problem, this paper is focused on increasing teacher creativity. Hence, the formulation of the problem is whether there is an improvement in teacher creativity through the implementation of audio-visual media at SMP Negeri 4 Dumai. In accordance with the background and formulation of the problem, this paper aims to increase the creativity of teachers in SMP Negeri 4 Dumai through the implementation of audio-visual media. This type of research is school action research (PTS) which aims to determine the success of teachers’ creativity improvement in teaching through the use of audio-visual media at SMP Negeri 4 Dumai. Based on the results of the analysis and discussion, it can be concluded that teacher creativity in teaching at SMP Negeri 4 Dumai can be increased through the use of audio-visual media. Thus, the teacher acceptance rate increased. Comparison of teacher creativity in teaching in cycle I increased in cycle II. If cycle I that achieved 65% was increased to 71.5% in cycle II.